Results from Cryo-PoF Project: Power over Fiber at Cryogenic Temperature for Fundamental and Applied Physics - Andrea Falcone; Alessandro Andreani; Claudia Brizzolari; Esteban Javier Cristaldo Morales; Maritza Juliette Delgado Gonzales; Claudio Gotti; Massimo Lazzaroni; Luca Meazza; Gianluigi Pessina; Francesco Terranova; Marta Torti; Valeria Trabattoni (Particles, 2025)
The Cryo-PoF project is an R&D project funded by the Italian Insitute for Nuclear Research (INFN) in Milano-Bicocca (Italy). The technology at the basis of the project is Power over Fiber (PoF). By sending laser light through an optical fiber, this technology delivers electrical power to a photovoltaic power converter, in order to power sensors or electrical devices. Among the several advantages this solution can provide, we can underline the spark-free operation when electric fields are present, the removal of noise induced by power lines, the absence of interference with electromagnetic fields, and robustness in hostile environments. R&D for the application of PoF in cryogenic environments started at Fermilab in 2020; for the DUNE Vertical Drift detector, it was needed to operate the Photon Detector System on a high-voltage cathode surface. Cryo-PoF, starting from this project, developed a single-laser input line system to power, at cryogenic temperatures, both an electronic amplifier and Photon Detection devices, tuning their bias by means of the input laser power, without adding ancillary fibers. The results obtained in Milano-Bicocca will be discussed, presenting the tests performed using power photosensors at liquid nitrogen temperature.